Clinical factors predicting treatment resistant depression: affirmative results from the European multicenter study. (5th October 2018) - Kautzky, A.; Dold, M.; Bartova, L.; Spies, M.; Kranz, G. S.; Souery, D.; Montgomery, S.; Mendlewicz, J.; Zohar, J.; Fabbri, C.; Serretti, A.; Lanzenberger, R.; et al.
Abstract : Objectives: Clinical variables were investigated in the 'treatment resistant depression (TRD)‐ III' sample to replicate earlier findings by the European research consortium 'Group for the Study of Resistant Depression' (GSRD) and enable cross‐sample prediction of treatment outcome in TRD. Experimental procedures: TRD was defined by a Montgomery and Åsberg Depression Rating Scale (MADRS) score ≥22 after at least two antidepressive trials. Response was defined by a decline in MADRS score by ≥50% and below a threshold of 22. Logistic regression was applied to replicate predictors for TRD among 16 clinical variables in 916 patients. Elastic net regression was applied for prediction of treatment outcome. Results: Symptom severity (odds ratio (OR) = 3.31), psychotic symptoms (OR = 2.52), suicidal risk (OR = 1.74), generalized anxiety disorder (OR = 1.68), inpatient status (OR = 1.65), higher number of antidepressants administered previously (OR = 1.23), and lifetime depressive episodes (OR = 1.15) as well as longer duration of the current episode (OR = 1.022) increased the risk of TRD. Prediction of TRD reached an accuracy of 0.86 in the independent validation set, TRD‐I. Conclusion: Symptom severity, suicidal risk, higher number of lifetime depressive episodes, and comorbid anxiety disorder were replicated as the most prominent risk factors for TRD. Significant predictors in TRD‐III enabled robust prediction of treatment outcome in TRD‐I.